(untitled) (Mustansiria Dental Journal, 2018)
Alpha - amylase is one of the major protein components of saliva. The main function of salivary alpha-amylase is the enzymatic digestion of carbohydrates, but it is also important for mucosal immunity in the oral cavity. The salivary enzyme alphaamylase has been proposed as a marker for stress-induced activity of the sympathetic nervous system. In the growing field of amylase research, recent studies have underscored the usefulness of salivary alpha-amylase in this regard. Fifteen Iraqi male students were considered in this study with mean age of 19.0 years old during examination period as stress students, another fifteen students without examination were considered as .control. α-Amylase assay were achieved by using colorimetric photometry method. The collected data predicted elevation of amylase level from 2354.260 ± 379.757 to 2817.977 ± 125.375 IU/L with a significant change. Positive correlation was recorded when plotted the correlations values of stress and no stress individual’s. In Conclusion we found that acute stress caused by examination associated with elevation of amylase in saliva significantly, however one of the main causes of academic stress is test anxiety for Undergraduate students seem to be more emotionally vulnerable due to examinations.